Detección de Betalactamasas de espectro extendido en Enterobacteriaceae en un Centro de Salud de Maracaibo, Venezuela - Perozo Mena Armindo; Marín Milagros; Castellano Maribel; Ling Toledo Eliana; Núñez Daniela; Ginestre Messaria; Villasmil Jessica; Bermúdez-González José; Villalobos Rafael; Gómez-Gamboa Liliana (Kasmera, 2017)
Abstract: The high incidence of the infectious diseases and the antimicrobial resistance arise represent a public health threat today. The extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae are an example of this phenomenon. We determined the ESBL-production in Enterobacteriaceae isolates from a Healthcare Center in Maracaibo, during September 2014 to February 2015. The Kirby-Baüer method was perform to preliminary phenotypic detection of ESBL, according to CLSI guidelines. ESBL-production was confirmed by a double-disk synergy test according to the CLSI standards. To genotypic confirmation, the genes blaCTX-M, blaTEM and blaSHV were amplified by PCR. Fifty-five (n=55) strains were analyzed distributed in Escherichia coli (56.36 %), Klebsiella pneumoniae (21.82 %), Enterobacter cloacae (7.27 %), Proteus mirabilis and Serratia marcescens (5.45 % each one), Salmonella spp. and Morganella morganii (1.82 % each one). The major encoded ESBL was the blaTEM gene (83.63 %); followed by 23.63% of the blaCTX-M gene, and 21.81 % encoded the blaSHV gene. 27.27 % of the isolates produced two or three ESBL simultaneously. These results confirmed the high spread of this resistant mechanism among Enterobacteriaceae-producing infections in our public health institutions, therefore control measures should applied to control and reduce its incidence.